Podjetništvo med priložnostjo in nujo: GEM Slovenija 2015 - Rebernik, Miroslav; Tominc, Polona; Crnogaj, Katja; Širec, Karin; Bradač Hojnik, Barbara; Rus, Matej (University of Maribor Press, 2016)
Entrepreneurship between Opportunity and Necessity : GEM Slovenia 2015. The Global Entrepreneurship Monitor (GEM) is the world’s most comprehensive research into entrepreneurship, focusing on the interrelatedness of entrepreneurship and economic development, providing detailed insights into the world of entrepreneurship and showing the current state of affairs in individual countries. As GEM methodology is the same all over the world it presents an invaluable source of information for the researchers and their scientific contributions. GEM provides a good understanding of societal values regarding entrepreneurship and individual entrepreneurship characteristics of individuals, such as their perception about business opportunities, the perception of their own capabilities to act entrepreneurially, their fear of failure, and their entrepreneurship intentions. Entrepreneurship activity is monitored throughout its various phases (nascent, new, and established businesses as well as business discontinuation). Some individuals decide to pursue entrepreneurship out of necessity, in order to survive, whereas others become entrepreneurially active to take advantage of a business opportunity. Present study shows a decrease in the number of necessity-driven entrepreneurs, which is good news, particularly because such entrepreneurs are, on average, less development-oriented; they employ less and are also less competitive.